A guide to game theory - Carmichael, Fiona (FT/Prentice Hall, 2005)
Almost every aspect of life presents us with decision problems, ranging from the simple question of whether to have pizza or ice cream, or where to aim a penalty kick, to more complex decisions like how a company should compete with others and how governments should negotiate treaties. Game theory is a technique that can be used to analyse strategic problems in diverse settings; its application is not limited to a single discipline such as economics or business studies. A Guide to Game Theory reflects this interdisciplinary potential to provide an introductory overview of the subject. Put off by a fear of maths? No need to be, as this book explains many of the important concepts and techniques without using mathematical language or methods. This will enable those who are alienated by maths to work with and understand many game theoretic techniques. KEY FEATURES Key concepts and techniques are introduced in early chapters, such as the prisoners' dilemma and Nash equilibrium. Analysis is later built up in a step-by-step way in order to incorporate more interesting features of the world we live in. Using a wide range of examples and applications the book covers decision problems confronted by firms, employers, unions, footballers, partygoers, politicians, governments, non-governmental organisations and communities. Exercises and activities are embedded in the text of the chapters and additional problems are included at the end of each chapter to test understanding. Realism is introduced into the analysis in a sequential way, enabling you to build on your knowledge and understanding and appreciate the potential uses of the theory. Suitable for those with no prior knowledge of game theory, studying courses related to strategic thinking. Such courses may be a part of a degree programme in business, economics, social or natural sciences.Fiona Carmichael is Senior Lecturer in Economics at the University of Salford. She has a wealth of experience in helping students tackle this potentially daunting yet fascinating subject, as recognised by an LTSN award for 'Outstanding Teaching' on her innovative course in game theory.